ronaldo7
  • ronaldo7
2x² -7x += 15 Help Please
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
ronaldo7
  • ronaldo7
Do you use the quadratic formula
lochana
  • lochana
2x^2 - 7x += 15 means 2x^2 - 7x = 2x^2 - 7x + 15
lochana
  • lochana
is it += or just =

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

lochana
  • lochana
I see. it is =.
lochana
  • lochana
no I don't use any formula
ronaldo7
  • ronaldo7
Im confused what
lochana
  • lochana
in your original post, you have typed 2x² -7x "+=" 15 .
ronaldo7
  • ronaldo7
Oh woops
lochana
  • lochana
that is why I said that
ronaldo7
  • ronaldo7
its suppose to be 2x² -7x = 15
ronaldo7
  • ronaldo7
sorry
lochana
  • lochana
2x² -7x -15= 0 2x^2 + (10x - 3x) -15=0 (2x^2 + 10x) - (3x +15)=0 2x(x + 5) -3 (x +5)=0 (2x-3)(x+5)=0
ronaldo7
  • ronaldo7
So you use factoring
lochana
  • lochana
sorry. I made a mistake there
lochana
  • lochana
2x² -7x -15= 0 2x^2 + (-10x + 3x) -15=0 (2x^2 - 10x) + (-3x +15)=0 2x(x - 5) -3 (x -5)=0 (2x+3)(x-5)=0
ronaldo7
  • ronaldo7
hold on im solving it all over again
lochana
  • lochana
yeah. I messed it:)
ronaldo7
  • ronaldo7
I got (x-5)(2x +3) so the same thing
lochana
  • lochana
you need to make -7x into 2 parts so that you can pull out common factors like I did before
ronaldo7
  • ronaldo7
then you set them both to zero and solve right?
lochana
  • lochana
yes. that's right.
lochana
  • lochana
and do you know why?
ronaldo7
  • ronaldo7
Would you have to check the answers since its a radical equation
ronaldo7
  • ronaldo7
Yeah I know why because to solve for y you must plug in 0 for x
ronaldo7
  • ronaldo7
I mean to solve for x you plug in 0 for y
lochana
  • lochana
because. in order to be 0 of a multiplication of 2 terms happens only when one of them is equal to zero. so we argue that if (x-5)(2x +3) =0 (x-5) or (2x+3) has to be zero
ronaldo7
  • ronaldo7
Oh yeah and that but would you ahve to check your answer since its a radical equation
lochana
  • lochana
are you still here?
lochana
  • lochana
2x² -7x -15= 0 2x^2 + (-10x + 3x) -15=0 (2x^2 - 10x) + (3x -15)=0 2x(x - 5) +3 (x -5)=0 (2x+3)(x-5)=0
lochana
  • lochana
today is a bad day:D

Looking for something else?

Not the answer you are looking for? Search for more explanations.